Recent Insights into the Role of Unfolded Protein Response in ER Stress in Health and Disease - Lindholm, Dan; Korhonen, Laura; Eriksson, Ove; Kõks, Sulev (Frontiers in Cell and Developmental Biology, 2017)
Unfolded stress response (UPR) is a conserved cellular pathway involved in protein quality control to maintain homeostasis under different conditions and disease states characterized by cell stress. Although three general schemes of and genes induced by UPR are rather well established, open questions remain including the precise role of UPR in human diseases and the interactions between different sensor systems during cell stress signaling. Particularly, the issue how the normally adaptive and pro-survival UPR pathway turns into a deleterious process causing sustained endoplasmic reticulum (ER) stress and cell death requires more studies. UPR is also named a friend with multiple personalities that we need to understand better to fully recognize its role in normal physiology and in disease pathology. UPR interacts with other organelles including mitochondria, and with cell stress signals and degradation pathways such as autophagy and the ubiquitin proteasome system. Here we review current concepts and mechanisms of UPR as studied in different cells and model systems and highlight the relevance of UPR and related stress signals in various human diseases.